2014
DOI: 10.1073/pnas.1410293111
|View full text |Cite
|
Sign up to set email alerts
|

Human TLR10 is an anti-inflammatory pattern-recognition receptor

Abstract: Toll-like receptor (TLR)10 is the only pattern-recognition receptor without known ligand specificity and biological function. We demonstrate that TLR10 is a modulatory receptor with mainly inhibitory effects. Blocking TLR10 by antagonistic antibodies enhanced proinflammatory cytokine production, including IL-1β, specifically after exposure to TLR2 ligands. Blocking TLR10 after stimulation of peripheral blood mononuclear cells with pam3CSK4 (Pam3Cys) led to production of 2,065 ± 106 pg/mL IL-1β (mean ± SEM) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
217
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(235 citation statements)
references
References 24 publications
12
217
5
1
Order By: Relevance
“…Briefly, lipoproteins are recognized by TLR1, TLR2 and TLR6; double-stranded and single-stranded RNAs by TLR3, TLR7 and TLR8; LPS by TLR4; flagellin by TLR5; and DNA by TLR9. 11 Although recent evidence suggests that TLR10 could have either immune-stimulatory 12 or immune-suppressive 13 properties, its exact activating ligand(s) and function are not yet known. TLRs signal through five different adaptor molecules: myeloid differentiation primary response gene 88 (MyD88), MyD88 adaptor-like (Mal), TIR-domain containing adaptor protein-inducing IFN-b (TRIF), TRIF-related adaptor molecule (TRAM) and sterile armadillo-motif-containing protein (SARM).…”
Section: Pathways Triggering Production Of Type-i-ifnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, lipoproteins are recognized by TLR1, TLR2 and TLR6; double-stranded and single-stranded RNAs by TLR3, TLR7 and TLR8; LPS by TLR4; flagellin by TLR5; and DNA by TLR9. 11 Although recent evidence suggests that TLR10 could have either immune-stimulatory 12 or immune-suppressive 13 properties, its exact activating ligand(s) and function are not yet known. TLRs signal through five different adaptor molecules: myeloid differentiation primary response gene 88 (MyD88), MyD88 adaptor-like (Mal), TIR-domain containing adaptor protein-inducing IFN-b (TRIF), TRIF-related adaptor molecule (TRAM) and sterile armadillo-motif-containing protein (SARM).…”
Section: Pathways Triggering Production Of Type-i-ifnsmentioning
confidence: 99%
“…Second, acting on the vascular and lymphatic system Type-I-IFNs inhibit angiogenesis through VEGF downregulation (9). Finally, acting on the immune system Type-I-IFNs may favor tumor regression by stimulating the maturation of DCs (10), promoting the release of pro-inflammatory cytokines (11), favoring CTL cross-priming (12), fostering the activation and survival of CD8 C and CD4 C T cells (13) and of NK cells (14), having a crucial role on core energetic metabolism regulation (15), and negatively regulating immune suppressive Treg cells (16) and MDSCs (17). CSC: cancer stem cell; DC: dendritic cell; EMT: epithelial-to-mesenchymal transition; IFNs: interferons; MDSC: myeloid-derived suppressor cell; MHC-I: major histocompatibility complex-I; NK: natural killer; PD1: programmed death 1; PD-L1: programmed death-ligand 1; TAAs: tumor-associated antigens; TCA: tricarboxylic acid; Treg: regulatory T cell; VEGF: vascular endothelial growth factor; VLS: vascular and lymphatic system.…”
Section: Cancer-intrinsic Effects Of Type-i-ifnsmentioning
confidence: 99%
“…Recent studies have suggested that the function of TLR10 differs from other TLRs, as it was shown to inhibit TLR2-driven innate immune activation [68][69][70]. By contrast, TLR10 has also been described as a stimulatory receptor in the innate immune recognition [ TLR6 sequence variant rs5743810 (Pro249Ser) leads to the substitution of proline for serine at amino-acid position 249 of the TLR6 protein.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…TLR6 sequence variant rs5743810 is associated with susceptibility to tuberculosis [16], complicated skin and skin structure infections [22], aspergillosis [23] and malaria [20]. [69][70]78]. How these TLR10 sequence variants precisely exert their effect remains unknown, but the location of rs4129009 in the LRR region and rs11096955 in the TIR domain could indicate involvement in the recognition of PAMPs or signal transduction, respectively.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…2009), Grimm et al (2010), Hasan et al (2005), Hornung et al (2002), Huen and Rook(2014),Nagase et al (2003),Oosting et al (2014) …”
mentioning
confidence: 99%